Karakteristik Tiwul Instan Subtitusi Ubi Jalar Kuning (Ipomoea batatas L.) sebagai Sumber β–Karoten - Herlina Herlina; Nita Kuswardhani; Ahmad Nafi'; Muhammad Syaiful Adzim (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
This study aims to examine the effect of percentage substitute of yellow sweet potato (Ipomoea batatas L.) on the physical, chemical and organoleptic characteristics of instant tiwul. It also aims to determine the exact percentage of yellow sweet potato in instant tiwul with high β-carotene content and favored by panelists. The completely randomized design (CRD) method was used with a single factor, namely the percentage substitution of yellow sweet potato (0, 10, 20, 30, 40, and 50%). Each treatment was repeated 3 (three) times while the data obtained were analyzed using the analysis of variance (ANOVA). In addition, when significant differences exist between treatments (α ≤ 0,05), the Duncan new multiple range test (DNMRT) is used, organoleptic data were analyzed using the chi-square test (α ≤ 0.05), meanwhile, to determine the best treatment, an effectiveness test was performed. The results showed that the percentage substitution of yellow sweet potato significantly affected the water content, total β-carotene content, rehydration and swelling power, bulk density, panelists’ preference for color, aroma, taste, texture, elasticity and overall. Based on the effectiveness test, the best percentage substitution of yellow sweet potato in instant tiwul production was P3 treatment (yellow sweet potato substitution by 30%), which has a total β-carotene content of 0.336 mg/100 g, panelists’ preference for color, aroma, taste, texture, suppleness, and overall of 28, 32,40, 32, 36, and 32% respectively.